Synthesis of Internal Geneva Combined Mechanism with Uniform Speed - Zhou Hongying; Han Jiguang (Jixie chuandong)
For the geneva mechanism,the kinematics coefficient of the geneva mechanism is a constant if the groove number of the ceneva wheel is a constant.The planetary transmission mechanism using as the drive crank of the geneva wheel is equal to the mechanism which has a variable length and a variable speed along the elliptical moving crank.Therefore the kinematics characteristics of the geneva mechanism can be changed.By using elliptic curve generated within the planetary transmission mechanism as the crank drive geneva mechanism,select mechanism parameters appropriately,can make thegeneva wheel movement in the middle with a uniform motion characteristics.The synthesis method of the combined geneva mechanism is put forward based on the kinematics coefficient.